Model Pembelajaran Gamifikasi dalam Meningkatkan Motivasi dan Keterlibatan Peserta Didik pada Era Digital: Kajian Teoretis dan Implementasinya dalam Pendidikan - Dony Agus Prasetyo; Joko Subando (TSAQOFAH, 2026)
The transformation of 21st-century education demands learning innovation that can improve students’ motivation, engagement, and learning outcomes. One relevant approach is the gamification learning model, namely the application of game elements in a learning context to create a more engaging, interactive, and meaningful learning experience. This study aims to examine the concept, characteristics, implementation steps, benefits, as well as the strengths and weaknesses of the gamification learning model in the learning process. This study uses a library research method by analyzing various relevant scholarly literature on gamification in education. The results of the review show that gamification can increase students’ intrinsic and extrinsic motivation through the use of game elements, such as points, badges, leaderboards, levels, rewards, and challenges. Gamification also encourages active participation, collaboration, healthy competition, and students’ critical thinking skills. The implementation of gamification can be carried out through various digital media, such as Kahoot, Quizizz, Wordwall, Educandy, Gimkit, and barcode scanners, adjusted to the learning objectives. Although it has various advantages, the implementation of gamification requires careful planning, technological readiness, and appropriate learning management so that the learning orientation does not shift merely toward the achievement of rewards. The conclusion of the study affirms that gamification can serve as an innovative learning model alternative that is relevant to the characteristics of students in the digital era. The implications of this study indicate that gamification contributes to improving the quality of learning processes and outcomes through active, contextual, healthy competitive, and meaningful learning experiences.